Konflik Bentuk-Bentuk Konflik Keluarga dalam Novel 00.00 Karya Ameylia Falensia: Pendekatan Sosiologi Sastra: Pendahuluan - Sijabat, Siska Geofani; Harahap, Nurhayati; Emma Marsella (Hasta Wiyata, 2024)
In daily life, the emergence of conflicts is common because each individual has different interests, goals, or opinions. When these interests, goals, or opinions do not align with each other, conflicts arise. Similarly, in family life, conflicts often occur among family members engaged in debates, quarrels, disputes, or arguments about various matters. This study aims to describe the forms of family conflicts found in the novel 00.00 by Ameylia Falensia. The method used in this research is a qualitative descriptive method. The data in this study consist of quotations from the content of the novel 00.00 by Ameylia Falensia that depict family conflicts through character interactions. Data collection techniques used in this study include library research, observation, and note-taking. The data were analyzed using content analysis techniques and employing a literary sociology approach. The data are presented in narrative form as each data is described based on the research findings. From the results of the study, various forms of family conflicts were found in the novel 00.00 by Ameylia Falensia. These forms of family conflict include: conflicts with parents consisting of conflicts between children and fathers and conflicts between children and mothers; conflicts with one's own children consisting of conflicts between fathers and children and mothers and children; conflicts with relatives consisting of conflicts between sisters and brothers, conflicts among sisters, and conflicts among brothers; conflicts between husbands and wives.